Citric Acid Improves Egg White Protein Foaming Characteristics and Meringue 3D Printing Performance - Huajiang Zhang; Shihui Hua; Mengzhuo Liu; Rui Chuang; Xin Gao; Hanyu Li; Ning Xia; Chaogeng Xiao (Foods)
Meringue has limited the use of meringue for personalization because of its thermally unstable system. Citric acid (CA) enhancement of egg white protein (EWP) foaming properties is proposed for the preparation of 3D-printed meringues. The results showed that CA increased the viscosity, exposure of hydrophobic groups (79.8% increase), and free sulfhydryl content (from 5 µmol/g to 34.8 µmol/g) of the EWP, thereby increasing the foaminess (from 50% to 178.2%). CA treatment increased the rates of adsorption, stretching, and orientation of EWP at the air–water interface to form multiple layers, resulting in a delay in foam thinning. The secondary structure of CA-treated EWP remained intact, and the exposure of amino acid residues in the tertiary structure increased with the expansion of the hydrophobic region. CA-treated EWP-prepared protein creams had a suitable viscosity (from 233.4 Pa·s to 1007 Pa·s at 0.1 s−1), shear thinning, structural restorability, and elasticity, which ensured good fidelity of their printed samples. Experiments involving 3D printing of CA-treated EWP showed that CA could significantly enhance the 3D printing fidelity of EWP. Our study could provide new ideas for the development of customizable 3D-printed foam food products.